RAHASIA BAHASA ARAB SEBAGAI KALAM ILAHI “Pakar Tafsir” - Ahda Islah Addiny dan Tutik Hamidah (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2022)
Arabic is the language of the Qur'an was chosen to be the divine word. So it is absolute if in understanding His message Arabic becomes one of the important knowledge. In addition, there are several theories stating that Arabic is the language of Heaven brought by the prophet Adam, but this theory is considered very weak because there is no concrete evidence. Starting from these questions, anxiety arises about what is the secret of the specialty of the Arabic language so that it is chosen to be divine kalam, what is the uniqueness of the Arabic language, to the question of the nature of kalam itself, both in the Arabic language or Arabic literature. So by using the analytical descriptive method, the author tries to describe the understanding of the uniqueness, secrets and nature of the meaning of kalam by reaching out to a literature review. So from this analysis, an understanding emerges that the uniqueness of the Arabic language is contained in the knowledge of Nahwu, Shorof and Balaghah. The Qur'an is not poetry, not poetry, and not prose like human language. But the miracle of the Qur'an, it really touches the mind and heart. Not only that, the language structure in the Qur'an is an unintentional sentence structure, purely from the divine word. While the arrangement of sentences in Arabic is an arrangement that is deliberately made like syi'ir.